A Technique for Transforming Rules in Deductive Databases - Mamat, Ali (Universiti Putra Malaysia Press, 1994)
In deductive databases the efficiency of recursive query evaluation is considered as an important goal. One approach to achieving this goal is to use methods that transform the original query into a new set of queries. One such method is magic sets. In the magic sets method, a query expressed by rules is transformed into a set of rules called magic rules. This paper shows how to perform this transformation by using a rule/goal graph data structure. The advantage of the technique used here is that it is very simple and clear.